Praxeological Analysis: A New Qualitative Methodology - Doug Hardman; Phil Hutchinson (International Journal of Qualitative Methods)
This paper introduces Praxeological Analysis (PA), a new qualitative methodology for investigating psychological phenomena by examining their situated sense within interaction and talk. PA draws upon and develops ideas from three intellectual resources: (i) praxeology, (ii) gestalt psychology, and (iii) the method of grammatical investigation found in the investigative ordinary language philosophy of Ludwig Wittgenstein. We integrate these three resources through the concept of linguistic gestalts , which serves as the foundation for PA. We argue that once psychological phenomena are respecified in terms of linguistic gestalts, the appropriate mode of investigation is what Wittgenstein termed grammatical. PA implements this mode of investigation by generating realizations through descriptions of actual, imagined, and fictionalized situations. The goal of such investigations is to explore the grammar—the practice-embedded rules for meaningful use—of psychological terms, as this reveals their real-world significance. In PA, we develop this insight into a structured methodology that qualitative researchers can systematically apply. By outlining the conceptual foundations of PA and demonstrating its methodological application, we position PA as a novel and transformative approach in qualitative research.